Impact Covid-19 on Implementation and Evaluation of Online Learning - Muhammad Isradi; Sumiyati Sumiyati (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Nearly 300 million students worldwide are disrupted in teaching and learning activities, and will threaten the rights of education in the future. The Covid-19 pandemic outbreak is a serious epidemic that must be dealt with by universities, as a result of this outbreak resulted in a change in the system of learning patterns that are ongoing. Mercu Buana University is preparing itself and adapting to face these uncertain conditions, one of which is setting up the system Perkuliahan Online Sementara / Temporer (POST) . So that the teaching and learning process and lectures can continue. Implementation of the system Perkuliahan Online Sementara / Temporer (POST) can be applied and used as a model to replace the conventional lecture system. Can be used as an evaluation in online learning, know the most dominant variable in influencing online learning